2017
DOI: 10.7759/cureus.1818
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of the Use of Intrathecal Morphine for Spinal Three Column Osteotomy

Abstract: IntroductionThe use of intrathecal morphine has the potential to help alleviate the pain that patients experience undergoing spinal surgeries. Complications can cause immobilization, which can lead to vascular thrombosis and ileus. Studies have shown epidural analgesia significantly lowered postoperative pain scores in scoliosis surgeries. Intrathecal anesthesia has been shown to have good pain control over the initial 24-hour postoperative period.PurposeDetermine if intrathecal morphine would reduce postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…These studies consistently reported that intrathecal morphine was correlated with reduced postoperative pain scores compared with standard of care. [7][8][9][10][11] Other studies have demonstrated that intrathecal opioids may decrease the use of patient-controlled analgesia (PCA). 12 However, the prevalence of intrathecal morphine side effects, such as delayed respiratory depression and urinary retention, may be significant and may last up to 24 hours.…”
mentioning
confidence: 99%
“…These studies consistently reported that intrathecal morphine was correlated with reduced postoperative pain scores compared with standard of care. [7][8][9][10][11] Other studies have demonstrated that intrathecal opioids may decrease the use of patient-controlled analgesia (PCA). 12 However, the prevalence of intrathecal morphine side effects, such as delayed respiratory depression and urinary retention, may be significant and may last up to 24 hours.…”
mentioning
confidence: 99%